Das margens ao centro?: refletindo sobre a teoria feminista e a sociologia acadêmica - (:unkn) unknown (Ministério Público do Estado da Bahia, 2003)
Several decades of feminist/gender studies in Brazilian universities have been fruitful and productive, and the national feminist publications that are a part of this scenario have played a fundamental role. Nonetheless, we still experience significant difficulties in bringing our feminist perspective into the mainstream of the social sciences. I engage here in a brief discussion of some of the reasons behind these difficulties. I also look at the role of one particular local feminist publication within this context, and what its role could be in furthering thein corporation of feminist discussions into social science programs and curriculum.
From the margins to the center?: thinking about feminist theory and academic sociology
Keywords: Teoria feminista; Estudo de gênero; Publicação feminista; Currículo das Ciências Sociais; CNPQ::CIENCIAS SOCIAIS APLICADAS::DIREITO